2014
DOI: 10.1099/mic.0.078527-0
|View full text |Cite
|
Sign up to set email alerts
|

Anionic lipids and the cytoskeletal proteins MreB and RodZ define the spatio-temporal distribution and function of membrane stress controller PspA in Escherichia coli

Abstract: All cell types must maintain the integrity of their membranes. The conserved bacterial membraneassociated protein PspA is a major effector acting upon extracytoplasmic stress and is implicated in protection of the inner membrane of pathogens, formation of biofilms and multi-drug-resistant persister cells. PspA and its homologues in Gram-positive bacteria and archaea protect the cell envelope whilst also supporting thylakoid biogenesis in cyanobacteria and higher plants. In enterobacteria, PspA is a dual functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Previous studies have observed the formation of 36-mers by E. coli PspA in vitro (Hankamer et al , 2004), supported by further data showing that PspA forms up to 36-mers in vivo (Jovanovic et al , 2014b). Similarly, in B. subtilis the Lia system contains a PspA homologue, LiaH, which has been shown to form large oligomeric rings (Wolf et al , 2010).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies have observed the formation of 36-mers by E. coli PspA in vitro (Hankamer et al , 2004), supported by further data showing that PspA forms up to 36-mers in vivo (Jovanovic et al , 2014b). Similarly, in B. subtilis the Lia system contains a PspA homologue, LiaH, which has been shown to form large oligomeric rings (Wolf et al , 2010).…”
Section: Discussionmentioning
confidence: 58%
“…This behaviour may aid in the stabilization of the B. pseudomallei cytoplasmic membrane during induction of the Psp-like response as a result of stressful conditions. Recently, it has been proposed that in E. coli PspA is potentially targeted to areas of the inner membrane associated with peptidoglycan biosynthesis machinery (Jovanovic et al , 2014b). In light of this, the presence of a gene encoding a penicillin-binding protein, mrcA , directly upstream of BPSL2105 may be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of fluorescent PspA indicated that the movement of oligomers is important for PMF preservation and depends on the cytoskeletal proteins MreB and RodZ (25,45). Therefore, it was suggested that PspA function relates to cell envelope organization, with links to peptidoglycan and phospholipid biogenesis (25,48). The molecular details of how this mechanism might work are unclear, and caution should probably be taken when interpreting the effects of mreB-or rodZ-null mutations because of the possibility of pleotropic effects on the cell envelope.…”
Section: Phage Shock Protein a Maintains The Proton Motive Forcementioning
confidence: 96%
“…The repressive PspF-PspA complex bound to psp promoter(s) on the DNA dynamically and transiently communicates with the IM under non-stress conditions. Under IM stress conditions, PspA dissociates from the PspF-PspA inhibitory complex and binds the stressed membrane as a higher order oligomer [7][8][9]. Under all experimental conditions, the PspF assembled and localized on the DNA as a single hexameric species, binding and activating a single psp promoter (pspA or pspG) at a time [7].…”
Section: The Cellular Landscape Of the Psp Response In E Colimentioning
confidence: 98%